Topologia de redes de interações entre aves e plantas no Brasil: nectarivoria na Mata Atlântica e Cerrado - Camacho, Vanessa Alcantara (Universidade Federal de São Carlos, 2025)
The Brazilian Savanna (Cerrado) and Atlantic Forest are two of the 25 global biodiversity hotspots, characterized by a high concentration of endemic species and significant habitat loss. Through the study of interaction network topology, it is possible to identify emergent properties at the community level that are not evident in interactions between individual organisms. In this study, we tested the hypothesis that the Atlantic Forest is more nested, modular, connected, and specialized than the Cerrado, exhibiting higher values for these metrics in mutualistic plant-hummingbird pollination networks. Data were collected through an advanced search of articles published on the Web of Science platform. We found 10 articles published between 2007 and 2023 on plant-hummingbird interaction networks, and all interactions were grouped into a matrix for each biome. Using RStudio (version 4.4.2), we constructed an interaction network for each biome and performed statistical analyses to compare the metrics of interest. We found that the tested metrics showed similar values for both biomes, although most were slightly higher for the Atlantic Forest, as expected. The networks exhibited low nesting but higher values for the Atlantic Forest (Cerrado wNODF = 1.351; Atlantic Forest wNODF = 1.401). Modularity was significant only for the Atlantic Forest, indicating a modular structure (Q = 0.518). Connectance was slightly higher for the Cerrado (Atlantic Forest C = 0.130; Cerrado C = 0.158), and the networks were highly generalist, though the Atlantic Forest was slightly more specialized (Cerrado H2’ = 0.039; Atlantic Forest H2’ = 0.044). Although the differences between the biomes are subtle, the Atlantic Forest tends to exhibit greater structural complexity in its plant-hummingbird interaction networks. However, further studies with larger datasets are needed to confirm these patterns and obtain more robust results.
Topology of bird-plant interaction networks in Brazil: nectarivory in the Atlantic Forest and Cerrado
Keywords: Nectarivoria; Biomas Brasileiros; Hotspots; Topologia de redes; Conservação; Nectarivory; Brazilian Biomes; Network Topology; Conservation; CIENCIAS BIOLOGICAS::ECOLOGIA